Ficus sytsmae (Moraceae), a new species from South America and the reinstatement of Ficus schiedeana - Mitidieri-Rivera, Nicole; Damián-Parizaca, Alexander (Phytotaxa, 2025)
Ficus sytsmae (Moraceae), a new species from South America, is described and illustrated. The new taxon is named in honor of Kenneth J. Sytsma, a distinguished professor at the University of Wisconsin-Madison, in recognition of his contributions to the understanding of Urticalean Rosids. This new entity resembles other members of the Ficus pertusa complex, particularly F. trachelosyce, but can be distinguished from the latter by its caudate leaf blade apex (vs. acuminate), truncate-cordate leaf blade base (vs. acute), longer laminas (10–24 cm vs. 8–15 cm), longer petioles (3.5–13 cm vs. 2–3.5 cm), longer stipules (10–17 mm vs. 6–10 mm), larger fig diameter (12–20 mm vs. 10–12 mm) and longer ostiole length (5–7 mm vs. 2–2.5 mm). The study also includes morphological comparisons with other phenotypically similar species. Given the high degree of morphological plasticity observed in the Ficus pertusa complex, we conducted two-dimensional (2D) geometric morphometric analyses to support our taxonomic conclusions. Variation in leaf lamina and fig shape supports the recognition of F. sytsmae as a morphologically distinct entity and further justifies the reinstatement of F. schiedeana, which had previously been treated as a synonym of F. pertusa and is herein recognized as a separate species. A line illustration of the new species, along with a distribution map depicting the type collection of F. sytsmae, its phenotypically similar species, and the reinstated species, are provided.